Self Disclosure Antara Ayah dan Anak Laki-laki Keluarga Broken Home - Rahman, Edwar Aulia (Jurnal Ilmiah Wahana Pendidikan, 2024)
Self Disclosure that occurs between father and son After divorce often goes badly. There are many factors that children experience regarding the non-implementation of self-openness, including past trauma, and a changed point of view for fathers after divorce. This research uses a qualinative descriptive method with phenomenological analysis, it will be developed using the theory of self-disclosure , so as to obtain concrete and precise results.